Non-profit housing: current trends in the European context and its specific value for the inward urban development in Switzerland. - Streit, Roman (My University, 2018)
The market share of social housing is around 6 % in Switzerland, while it amounts to an average of 11 % across the countries of the EU-28. Between the countries, big differences in market shares and support schemes for social housing exist. This paper investigates these characteristics of social housing in Europe as well as its trends in the recent years. The situation of social housing in Switzerland in the European context is highlighted with a special focus to the aspect of inward urban development. It is shown, that market shares of social housing are generally declining in Europe. Parallely, there has been a shift from bricks and mortar subsidies towards housing allowances and a focus on clearer targetting of the remaining social housing stock towards those most in need. While this can be seen as a necessity to reach a high effectiveness of social housing, it has led to an increased concentration of economically and socially disadvantaged people in the remaining housing stock, raising concerns about ghettoisation that contradict the housing paradigm of socially mixed neighbourhoods. In Switzerland, social housing is partly clearly targeted at certain population parts (continously subsidized housing), but partly also open for all people (mostly social cooperative housing). This raises questions about the fair distribution of public housing subsidies, but also reflects the large variety of different social housing providers in the country. Moreover linking the subject of social housing and spatial planning it is shown, that social housing providers play an important role in the national spatial strategy of inward urban development. Using the example of the city of Zurich, which has the biggest social housing market share (24 %) of any Swiss municipality, success factors in this regard are examined. It is detected, that a continous cooperation between the city authorities and social housing providers is a key factor for a succesful linkage of housing policies with urban development. The strategy builds upon a set of housing support measures from the city with clear requirements for compensatory measures by the social housing providers that further the quality and effectiveness of social housing projects.
Keywords: Sozialer Wohnungsbau; Wohnungsmarkt; Sozialwohnung; Wohnbauförderung